Analisis Sektor Ekonomi Basis Dan Kependudukan Kabupaten Lingga - Mita Apriana (Jurnal Archipelago, 2024)
In planning for development, it is crucial to focus efforts on sectors that can significantly contribute to the region's economic growth and the improvement of the quality of life of its people. Therefore, evaluating the main economic sectors becomes key. This study aims to identify the key sectors in Lingga Regency, located in the Riau Islands Province, that serve as pillars of the economy. The method applied in this research is quantitative, using the Location Quotient (LQ) analysis technique, shift-share analysis, and aggregate trendline technique to process data. According to the findings, sectors considered as the backbone of the economy in Lingga Regency include agriculture, forestry, and fisheries; wholesale and retail trade, including repair of motor vehicles and motorcycles; information and communication; real estate; public administration; defense and social security; education; health and social services; and other service sectors. Progressive improvements in various sectors indicate potential growth in the future. Another finding predicts that the population of Lingga Regency will increase to 92,381 people by 2025, opening a significant market opportunity for the marketing of agricultural products, fisheries, and various other goods and services. The industrial sector, electricity, gas, and water supply in Lingga Regency show an increasing trend, while sectors such as agriculture, plantations, forestry, hunting, and fisheries are expected to decline. This study aims to provide recommendations to local governments in designing development programs for base and non-base sectors and labor management to spur economic growth in Lingga Regency.